Formação do carbonato de glicerol por transesterificação catalítica heterogênea - Paula, Gustavo Medeiros de (Universidade Federal de São Carlos, 2022)
The industrial production of biodiesel has generated large amounts of glycerol, transforming this co-product into raw material for other processes. Notably, glycerol carbonate has emerged as a promising substance for the chemical industry, since it is a biomass-derived product and has several applications. Glycerol carbonate can be produced by different processes, with the transesterification between glycerol and dimethyl carbonate being the most widely studied reaction. However, despite being considered the simplest and greenest possible route, other esters can be used, which makes the transesterification process chemically and operationally complex, despite this complexity not being properly disclosed. Therefore, in order to understand the process from a molecular catalysis perspective, this work investigated the reactions between glycerol and different carbonic acid esters (dimethyl carbonate, diethyl carbonate, ethylene carbonate and propylene carbonate), using CTA MCM-41 hybrid silica as basic catalyst. Furthermore, for comparison with the hybrid silica, the catalytic potential of calcium oxide (CaO) and magnesium oxide (MgO) was evaluated. The hybrid silica was synthesized according to a well-established method and the high-purity oxides were commercially purchased. The reactions for formation of glycerol carbonate were performed in a batch reactor, in the presence of dimethylformamide (DMF) as solvent. Experiments were performed to study the effects of different operational parameters on the formation of glycerol carbonate and co-products. The reaction products were analyzed by GC-FID and GC-MS and all chemical species produced during the reactions were identified. Reaction steps and reaction mechanisms were proposed for these reactions, together with determination of the conditions to produce glycerol carbonate with maximum efficiency in terms of conversion, selectivity, and yield. The results showed that hybrid silica has high catalytic activity, being more active than commercial catalysts. The main products of the reactions were glycerol carbonate and glycidol, with small amounts of glycerol monocarbonates, glycerol tricarbonates and glycidol carbonates being produced. Cyclic-chain esters showed greater reactivity than straight chain esters, forming fewer co-products. Finally, cyclic-chain esters and straight-chain esters formed the products following different reaction mechanisms.
Glycerol carbonate formation by heterogeneous catalytic transesterification
Keywords: Carbonato de glicerol; CTA-MCM-41; Ésteres do ácido carbônico; Glicerol; Transesterificação; Carbonic acid esters; Glycerol; Glycerol carbonate; Transesterification; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA